Certificação ambiental no Rio Grande do Sul: uma questão mercadológica, de marketing ou consciência ecológica - Schumacher, Luci Ines (2011)
This work presents a research on the subject of environmental certification, as well as deployment and maintenance of an Environmental Management System (EMS) in organizations. Faced with a visible degradation suffered by the environment and the fight for increasingly aware consumers in search of green products, there is the concern of employers, as a condition of survival and the acquisition of environmental certification in order to gain new markets and fit within the rules that facilitate the achievement of investment. This research study aims to analyze the current status of NBR ISO 14001 in certified companies in Rio Grande do Sul/Brazil that were certified in 2005, showing the reasons which led them to obtain and maintain or not the certification and verify that the reasons for seeking certification are related to market needs, marketing and environmental awareness. The methodology used in the study was descriptive, qualitative and quantitative and survey, using a structured questionnaire for data collection. The questionnaire was sent to certified companies and it had a returno 41 questionnaires that were sent to certified companies, showing the context in which they operate and purpose of organizations regarding ISO 14001 certification. From the analysis of research material it was concluded that the main motivator focus on obtaining and maintaining the ISO 14001 in environmental certification is a marketing question, which gained strength from recent environmental requirements coming from the stakeholders.